2012
DOI: 10.1016/j.jamda.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Barriers to Performing Nonpharmacological Interventions for Behavioral Symptoms in the Nursing Home?

Abstract: OBJECTIVE Behavioral symptoms are common in persons with dementia, and nonpharmacological interventions are recommended as the first line of therapy. We describe barriers to conducting nonpharmacological interventions for behavioral symptoms. DESIGN A descriptive study of barriers to intervention delivery in a controlled trial. SETTINGS The study was conducted in 6 nursing homes in Maryland. PARTICIPANTS 89 agitated nursing home residents with dementia. INTERVENTION Personalized interventions were deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 31 publications
1
45
0
6
Order By: Relevance
“…In fact, pain is thought to be one of the most important causal factors of BPSD 5. However, this causal link is often difficult to identify due to the complexities of BPSD, which change over the stages of dementia and are more frequent in the later stages of the disease 6. BPSD arising as a result of pain, such as agitation and aggression, can be extremely distressing for both the individual and their caregiver, and can lead to the inappropriate prescribing of antipsychotic medication instead of adequate pain treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, pain is thought to be one of the most important causal factors of BPSD 5. However, this causal link is often difficult to identify due to the complexities of BPSD, which change over the stages of dementia and are more frequent in the later stages of the disease 6. BPSD arising as a result of pain, such as agitation and aggression, can be extremely distressing for both the individual and their caregiver, and can lead to the inappropriate prescribing of antipsychotic medication instead of adequate pain treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Burns and McIlfatrick (2015) literature review identified that caregivers find it difficult to differentiate between behavioural change due to pain or other problems, such as, delirium. Cohen-Mansfield et al(2012) in an earlier study also found that pain is under recognised which results in an over prescribing of anti-psychotic medication and an under prescribing of analgesia. The implication for practice is that incorrect assessments of resident's behaviour could overlook pain as a cause of changes in behaviour and result in the administration of potentially harmful medication that increases agitation.…”
Section: Discussionmentioning
confidence: 92%
“…The findings from this study can guide strategies to address project barriers and maximize project facilitators. 23 Nurses have an influential role in leading initiatives to improve quality of care for residents. Staff development and education were found to be perceived by staff as important to project success, and QI training could potentially be improved by including research findings that address staff experiences with QI project implementation.…”
Section: Discussionmentioning
confidence: 99%